Enhanced Skin Deposition of Betamethasone Dipropionate from a Novel Formulation and Drug Delivery Technology - Zoe Diana Draelos; Matthew M. Draelos; Fraser Steele; Michelle Georgiou; Morten Praestegaard (Adis, Springer Healthcare, 2023)
Abstract Introduction Effective topical drug delivery is the essence of dermatologic treatment. The drug must be applied to the skin surface, be released from the vehicle, enter the stratum corneum, traverse the epidermis, and enter the dermis pharmacologically intact. New advances have improved emulsion-type formulation and drug delivery technology by encapsulating dispersed oil droplets in a robust multimolecular aqueous film of surfactants, oil, and water, enabling a multifold decrease in surfactant concentration compared to conventional creams. In the research reported here, we studied this new concept, termed polyaphron dispersion (PAD) technology, by comparing skin delivery of betamethasone dipropionate from a novel oil-in-water emulsion system of calcipotriene and betamethasone dipropionate (CAL/BDP) cream to that from a traditional topical suspension (CAL/BDP TS) utilizing in vitro and in vivo detection methods. Methods The amount of BDP released from the CAL/BDP cream and CAL/BDP TS was evaluated using both in vitro Franz cell analysis and in vivo human tape stripping from ten female human volunteers after a single application of CAL/BDP cream or CAL/BDP TS. For the tape stripping analysis, 20 circular tape strips were taken from forearm application sites at 1, 2, 4, and 8 h after application and analyzed for the amount of BDP in the tape strip using liquid chromatography-mass spectrometry (LC-MS). Results The in vitro Franz cell analysis demonstrated that the cumulative amount of BDP that diffused through the epidermis was statistically significantly greater for the CAL/BDP cream compared to the CAL/BDP TS at all time points. In addition, consistently higher amounts of BDP were recovered following CAL/BDP cream application than following CAL/BDP TS application at 1, 2, 4, and 8 h following application utilizing the in vivo tape stripping technique. Conclusion The novel PAD technology-based cream formulation delivered more BDP into the upper stratum corneum and lower epidermis than a traditional topical suspension.